2011
DOI: 10.3109/17453674.2011.566137
|View full text |Cite
|
Sign up to set email alerts
|

No benefit of a proximal stem centralizer in cementing of a femoral prosthesis in human cadavers

Abstract: Background and purposeA proximal stem centralizer may be beneficial regarding cementing pressures, cement penetration, and stem alignment. We measured these parameters when cementing a mat-surfaced femoral component with and without the use of a proximal stem centralizer.Material and methods8 femoral prostheses with proximal centralizers and 8 femoral prostheses without proximal centralizers were cemented according to third-generation cementing technique in 8 pairs of embalmed cadaveric femora. We recorded int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The maximum pressures in this study were similar to those reported in previous studies. 7,10,11 Pressurisation of cement influences the cement-bone interface. Pressures during stem implantation can be much higher than pressures during cementation, but do not affect cement interdigitation or blood displacement, as the cement is too viscous at this time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum pressures in this study were similar to those reported in previous studies. 7,10,11 Pressurisation of cement influences the cement-bone interface. Pressures during stem implantation can be much higher than pressures during cementation, but do not affect cement interdigitation or blood displacement, as the cement is too viscous at this time point.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of proximal cement pressurisers mainly focus on pressures generated (rather than pressures generated in each Gruen zone). [6][7][8] Two commonly used types of cement pressurisers are the Exeter MIS half-moon femoral cement seal (Stryker Orthopedics, Mahwah [NJ], USA) and the femoral canal pressuriser (Stryker Orthopedics, Mahwah [NJ], USA). The latter is designed to fit into the medullary canal of the proximal femur ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, despite the lack of impact on stem alignment, it was noted that a distal centralizer allows for less variation in the circumferential cement mantle compared with stems inserted without centralizers 123 . Petruskevicius et al assessed the impact of proximal stem centralizers on cementing pressure, penetration, and stem alignment and found no benefit in cement penetration and pressurization while posing an increased risk of stem malpositioning with the use of a proximal centralizing device 124 . These combined findings question the need for a centralizer, and surgeons are advised to pay close attention to stem positioning when using these devices, without relying on self-correction of erroneous stem alignment.…”
Section: Application and Insertion Factorsmentioning
confidence: 99%